Efficient Market Analysis of Jakarta Islamic Index (2019-2023) - Rahma Aulia Sidik; Wiku Suryomurti; Soon Yong Ang (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2024)
This study aims to analyze the efficient market form of the Jakarta Islamic Index. The methodology used is an event study with a window period of 20 days, including ten days before and ten days after the announcement of composition changes held twice a year. The sample consists of 102, with 30 companies listed during the study period and 36 companies excluded and re-listed following the composition change announcements. The analysis technique used is the Paired Sample T-test. The findings reveal no differences in abnormal returns and trading volume activity before and after the announcement. This suggests that the market had already absorbed the announcement information before the event, resulting in a weak reaction and indicating that the announcement did not significantly impact the Jakarta Islamic Index. This implies that the index operates in a semi-strong form of market efficiency. Consequently, companies listed in the index may need additional strategies to improve their stock performance. To provide further insight, this study also examines the average stock trading activity of companies that enter and exit the composition of the Jakarta Islamic Index for the 2019-2023 periods.